Female agency and documentary strategies subjectivities, identity and activism - Ulfsdotter, Boel 1959-; Backman Rogers, Anna 1981- (Edinburgh University Press, 2018)
Female Agency and Documentary Strategies centres on how self-portraiture and contemporary documentary manifestations such as blogging and the prevalent usage of social media shape and inform female subjectivities and claims to truth